How to prevent skin damage from air pollution part 2: Current treatment options - Damevska, Katerina; Simeonovski, Viktor; Darlenski, Razvigor; Damevska, Stefana (Hindawi Limited, 2021)
In the first part of this review, we have summarized the methods used to examine skin exposure to air pollution and the fundamental concept of skin-exposome interactions. Part 2 of this review focuses on dermatoses, whose aggravation or initiation by air pollution has been confirmed in evidence based medicine manner. Based on the model of photodermatology and photodermatoses, we propose a new concept of "polludermatoses." A key feature of this concept is identifying patients at risk, which will reveal the noxious effects of air pollutants on skin health. Identifying clinical signs of pollution-damaged skin could be beneficial in categorizing conditions caused or exacerbated by exposure to air pollution. Finally, we discuss the current treatment options and the pathogenetic processes targeted by these therapeutics or the development of novel treatment modalities.
Keywords: skin; air pollution; treatment